"I'd rather we be neighbours than lovers": The two-sidedness of multiculturalism. (July 2015) - Ng Tseung-Wong, Caroline; Verkuyten, Maykel
Multiculturalism can be viewed as promoting positive intergroup relations in the public domain (neighbours, classmates) and heritage culture maintenance in the romantic domain (marriage). The present study examined this "two-sidedness" of multiculturalism by focusing on intergroup social distance in relation to endorsement of multiculturalism, group identifications, and group status. The study was conducted in Mauritius amongst 1, 784 adolescents from the three main ethnic groups, Hindus ( n = 844), Muslims ( n = 630), and Creoles ( n = 310). In agreement with the "two-sidedness, " participants made a distinction between public and romantic social distance, and intergroup differentiation in social distance was stronger in the romantic compared to the public domain. The endorsement of multiculturalism was associated to lower out-group public distance and lower in-group romantic distance. National identification predicted lower public and romantic out-group social distance. Ethnic identification was associated with higher out-group social distances and lower in-group social distances, particularly for the high-status group of Hindus.